Interactome based identification and validation of prefoldin 5-α for prognosing CNS leukemia in B-ALL patients - Tessy Xavier; Lakshmi Sumitra Vijayachandran; Rumamol Chandran; Ullas Mony; Anitha Augustine; Neeraj Sidharthan; Rema Ganapathy; Pavithran Keechilat; K R. Sundaram; Krishnakumar N. Menon (Scientific Reports, 2022)
Abstract We report here the identification and validation of prefoldin 5-alpha (PFDN5-α) for the first time as prognostic biomarker for prediction of central nervous system (CNS) leukemia of B cell acute lymphoblastic leukemia (B-ALL) origin. Since cerebrospinal fluid (CSF) cytology being the gold standard of diagnosis for CNS leukemia with poor sensitivity, mandatory prophylactic intrathecal chemotherapy is administered irrespective of patients develop CNS leukemia. Thus, using interactome studies, we identified PFDN5-α as a prognostic biomarker for predicting CNS leukemia by interacting lymphoblastic proteins and CSF from B-ALL patients using far-western clinical proteomics approach. Validation by both western and ELISA methods confirmed our results. For further clinical translation, we performed Receiver Operating Characteristic (ROC) curve analysis generated from CNS +ve (n = 25) and −ve (n = 40) CSF samples from B-ALL patients and identified PFDN5-α-CSF reactivity cut-off value as 0.456. Values below 0.456 indicate the patient is at risk of developing CNS leukemia and suggestive of having intrathecal chemotherapy. Further flow cytometry validation for CNS leukemia positivity revealed that with increasing blast cells, a decrease in PFDN5-α-CSF reactivity confirming ELISA based PFDN5α-CSF reactivity assay. Predicting CNS leukemia development risk by ELISA based PFDN5-α-CSF reactivity assay could have potential in the clinical management of CNS leukemia.